Students Perception On The Implementation Of Blended Learning In Learning English Language - Noraisah Nurul Fatwa, Mohd Razali; Rosnani, Ismail (2018)
The implementation of blended learning in learning English Language is very useful to both teachers and students. This study shed light on exploring Universiti Malaysia Pahang students’ perceptions regarding the implementation of combining the features of face-to-face instruction and online learning by using Edmodo in their Fundamentals of English classes. For the achievements of these purposes, 30 students were involved in completing the open-ended questionnaires. The result of this research shows many positive signs in the students because the implementation of blended learning provide positive feedbacks and satisfaction in the teaching and learning processes. This study manages to support that through blended learning, the course and activities became more interesting and bring changes in the class as well. The technology also help the students in enhancing their language skills especially for reading and writing skills. They also learn new vocabulary and help to increase their fluency. The results demonstrate that blended learning might have a better impact on the students’ level of engagement since most of the research participants rated themselves as more engaged in this blended learning rather than in a traditional classroom practice. In addition, another finding shows that the language skills could be also improved by integrating the tremendous advancement of technology as a part of language acquisition in the class. Keywords: Blended learning, online learning, technology, language